DESIGN AND DEVELOPMENT OF HUNTER PLACES DOCUMENTARY VIDEOS IN BATAM AS A DARK TOURISM PROMOTION MEDIA - Hendi Sama; Felix Agusta Putra (Universitas Internasional Batam, 2022)
Tourist destinations are zones that are directly designated and advertised as tourist destinations. All tourism products are offered to a particular group of tourists who want to visit places containing a mystery and know the event's meaning. This can be found in historical places according to local people's stories. The development of dark tourism can increase foreign tourist visits, which can be used as an economy related to the government by attracting foreign tourists who want to provide foreign exchange for dark tourism, including remote areas. The author uses the flow of literature study and conducts research and development analysis to determine tourists' interest in visiting these places. After getting strong interest from the tourists, the researcher designed and built the appropriate video for it. This continues and is improved up to the implementation stage and ends at the dissemination stage. Many still do not understand how to attract tourists' attention from dark tourist destinations, whether it is shooting a film in the form of a vintage colour gradation video with a frame. The result of the design and development is a documentary video of dark tourism that the Indonesian people can use to attract foreign tourist visits to Indonesia.